Student companion to accompany fundamentals of biochemistry : life at the molecular level - Uzman, Akif (John Wiley & Sons, 2012)
Voet and Pratt's 4th edition of Principles of Biochemistry, challenges readers to better understand the chemistry behind the biological structure and reactions occurring in living systems